Research, Promotion and Tenure Guidelines for Academic Librarians: An Analysis of the Vague Expectations in Canadian University Collective Agreements - Power, Helen; Wheatley, Amanda (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2025)
Renewal, promotion, and tenure (RPT) are often the most stressful career milestones an academic librarian can face. These events can dictate the course of a librarian’s career. It would stand to reason that RPT guidelines would be thorough and exhaustive in order to better help librarians achieve these milestones. The purpose of this paper is to identify the requirements for academic librarians to receive RPT and determine how they align with standards of assessment for job performance. The authors reviewed libraries in Canada’s U15 Group of Research Institutions for any collective agreements or regulations documenting the RPT process. Eleven of the fifteen institutions had public facing documents, and each of these universities require successful job performance in professional practice, research, and service in order to achieve RPT. The authors apply the Management by Objective (MBO) practice to the findings to better understand how RPT guidelines can be improved to help librarians achieve these career milestones.